Mutu Kimia Dan Organoleptik Pempek Ikan Lele Dengan Subtitusi Tepung Buah Mangrove (Rhizophora mucronata) - Potabuga, Chandra; Mile, Lukman; Yusuf, Nikmawatisusanti (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to analyze the effect of mangrove flour substitution on the quality of pempek made from catfish which includes organoleptic (hedonic) and chemical quality. This research consists of formulation, hedonic organoleptic characteristics, selected products and chemical characteristics of selected products. The treatment in this research was the substitution of mangrove flour for tapioca flour with concentrations of 10g, 15g, and 20g. This research was designed using Kruskal Wallis to obtain hedonic organoleptic data and analyzed using Nonparametric Tests K Independent Samples. The analysis results were continued with Duncan's further test. Determination of selected products is carried out using the Bayes test. The results showed that pempek made from tapioca flour with the substitution of 10g, 15g and 20g mangrove flour had a significant effect on all organoleptic (hedonic) parameters, except appearance. Based on the analysis of the selected products, it was found that the pempek product with 15 g of mangrove flour substituted had chemical characteristics, namely a protein content of 10.44%; water content 40.43%; fat content 20.72%; ash content 1.79%; and carbohydrate content 26.63%. Meanwhile, the chemical test results for control or without substitution of mangrove flour were protein content 7.77%, water 37.54%, fat 28.38%, ash 1.11% and carbohydrates 25.21%.